The role of remittances in financing the current account deficit: The case of Serbia - Božidar Čakajac; Nenad Janković; Stevan Luković (Naše gospodarstvo / Our Economy, 2023)
Migrations of the resident population in Serbia, with the Western European countries as the main destination, have influenced remittances becoming an important source of income from abroad. Relevant economic literature, as well as the influential views expressed in the international financial institutions' reports, indicate that remittances are a more stable type of inflow of funds from abroad to developing countries compared to other types of capital movements. In addition to the positive economic effects of remittances, they also play a significant role in the balance of payments deficit reduction. The subject of this research refers to the examination of the role of remittances in financing the current account deficit in Serbia. The research goal is to explore whether the importance of remittances as a factor in the balance of payments deficit reduction in Serbia increased in the period 2007-2021. The results of the research show that remittances have become an important factor in current account deficit reduction in Serbia during the observed period.
Keywords: F24; F32; 330; Migrations; Remittances; Current account; Balance of payments; Serbia